Advanced acromegaly: successful disease control for more than 16 years using octreotide LA. (24th December 2020) - Elshafie, Omayma; Woodhouse, Nicholas
Summary: A 79-year-old male presented with a 10-year history of intermittent headache, sweating, persistent hand numbness and uncontrolled hypertension. He was receiving Nifedipine and Hydrochorothizide. On examination (O/E), his BP was 180/100 he was acromegalic. His growth hormone (GH) was 10 mIU/L (0.0–0.1) and his insulin-like growth factor (IGF-1): 952 µg/L (76–160). An MRI of the pituitary revealed a 3 × 2 cm pituitary macroadenoma. Surgery was refused and the family agreed for a therapeutic trial of octreotide. His GH levels fell immediately. Two weeks later he was switched to long-acting monthly octreotide in September 2003. During his 16-year follow-up, he has remained well and asymptomatic off medications for hypertension. His BP and IGF-1 levels were also normal until octreotide Long acting (LA) octrotide was stopped for 3 months at age 96. During this period the IGF-1 level returned to pretreatment levels 500 ng/L (50–141), GH 24 mIU/L (0.0–0.1), and a small residual tumour 0.5–0.8 cm was seen on the MRI. Octreotide LA was restarted and the IGF-1 and GH levels returned to normal. He continues the same treatment to date age 97 without side effects. We conclude that the successful control of IGF-1, GH levels, hypertension, tumour size and clinical symptoms for more than 16 years occurred using octreotide LA in an elderly advanced acromegalic patient. To the best of our knowledge, this is the first report of the successful use of octreotide LA for more than 16 years. Learning points: The value of a therapeutic trial of octreotide to identify responders. Control of GH and IGF-1 secretion using octreotide LA. The report of the successful use of octreotide for more than 16 years irrespective of age.